The conversation : a revolutionary plan for end-of-life care - Volandes, Angelo E., 1971- (Bloomsbury, 2015)
"There is an unspoken dark side of American medicine: keeping patients alive at all costs. Two thirds of Americans die in healthcare institutions tethered to machines and tubes, even though research indicates that most prefer to die at home in comfort, surrounded by loved ones. The question 'How do you want to live?' must be posed to the seriously ill because they deserve to choose. If doctors explain options--including the choice to forego countless medical interventions that are often of little benefit--then patients can tell doctors how they wish to spend the remainder of their lives"--Provided by publisher.